A comparative analysis of taxation and revenue trends in the Middle East and North Africa (MENA) region. Issue 4 (4th November 2019) - Alsharari, Nizar Mohammad
Abstract : Purpose: The purpose of this paper is to gain insight into how well past reforms have performed against revenue, equity and efficiency benchmarks of tax policymaking, so that the direction of future reform of tax system might be determined. It also presents a comparative analysis of taxation and revenue trends in the Middle East and North Africa (MENA) region over the data set period 1990-2012. Design/methodology/approach: By overviewing the development and relative significance of resource revenues, allocating non-resource taxes and examining the tax policies of constituent countries, this paper presents a comparative review of taxation and revenue trends in the MENA region. Findings: Findings showed, on average, a slight decline in non-resource revenues against the significant rise in income from resources. The analysis of government revenues and current taxation structures provide insight into how prior reforms have performed against the standard measures of tax policy-making (i.e. revenue, equity and efficiency) and directions for change leading to the establishment of simple tax systems. The study observes regional differences, such as the higher tax and revenues of the Maghreb sub-region over the Mashreq, except for value-added tax, where low rates were associated with equal or greater revenue. Similarities were also found, including the partial compensation by income taxes (not indirect taxes) for revenue lost through trade liberalization. The challenges of tax reform are found to vary across countries and opportunities for improving equity and reducing the complexity of tax systems across the region are identified. Research limitations/implications: Reforms in all tax systems could have major implications for the country, employment, earnings and tax revenues; but recommendations would require political value judgments and government decisions. The study suggests eliminating the current tax system, thereby replacing one of the more distortionary taxes in the current system with a neutral and efficient tax. Originality/value: The paper signals the need, even of the oil-rich states of the Gulf Cooperation Council, for governments to build tax systems capable of capturing and spending revenues effectively into the future.